Aplikasi Peramalan Jumlah Pendaftaran Siswa Di SMA IT IQRA’ Kota Bengkulu Menggunakan Metode Weight Moving Average (WMA) - Indah kartika; Sapri Sapri; Jhoanne Fredricka (UNIVED Press, 2023)
Abstract- Acceptance of new students is a routine activity every academic year that is carried out at school. IT IQRA' High School in Bengkulu City is one of the private schools in Bengkulu City which accepts new students every Academic Year. Based on data obtained from the 2018/2019 Academic Year to the 2022/2023 Academic Year (data attached), it shows that the level of the number of students sometimes decreases and also increases. This fluctuating pattern of student numbers is a problem faced by the school. IT IQRA Senior Middle School' Bengkulu City in determining the strategic steps and policies of the school in dealing with the Acceptance of New Students each Academic Year. The application for forecasting the number of enrollment students at IT IQRA' High School Bengkulu City was built using the Visual Basic .Net programming language and SQL Server 2008r2 Database. the forecasting application for the number of student enrollments at IT IQRA' High School in Bengkulu City is an application that can help schools find out how many new student enrollments will be in the coming school year based on the results of an analysis conducted from previous trend data using the Weight Moving Average Method. From the sample data used in the 2018/2019 Academic Year to 2022/2023, the forecast results obtained for the number of new student enrollments in the 2023/2024 Academic Year were 249 new students.